A Twenty-Five Year Review (1967-1991) of Epidemiological Profile and Trends of Selected Diseases - Jesus Sarol (Philippine Institute for Development Studies (PIDS), 1995)
This paper deals with the epidemiological trends and incidence of selected leading diseases in the country. Mortality rates and morbidity rates are investigated. It also offers recommendations for future policies and programs.
Keywords: 330; hospital care; mortality rate; morbidity rate; incidence analysis